2017
DOI: 10.7554/elife.22311
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the hijacking of endosomal sorting nexin proteins by Chlamydia trachomatis

Abstract: During infection chlamydial pathogens form an intracellular membrane-bound replicative niche termed the inclusion, which is enriched with bacterial transmembrane proteins called Incs. Incs bind and manipulate host cell proteins to promote inclusion expansion and provide camouflage against innate immune responses. Sorting nexin (SNX) proteins that normally function in endosomal membrane trafficking are a major class of inclusion-associated host proteins, and are recruited by IncE/CT116. Crystal structures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
80
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 60 publications
(99 reference statements)
3
80
0
Order By: Relevance
“…Another pathogenic protein that has been extensively characterized is the Chlamydial effector protein IncE. Chlamydiae infection leads to human blindness, respiratory and genital tract diseases.…”
Section: Manipulation Of Endosomal Protein Sorting By Pathogensmentioning
confidence: 99%
See 3 more Smart Citations
“…Another pathogenic protein that has been extensively characterized is the Chlamydial effector protein IncE. Chlamydiae infection leads to human blindness, respiratory and genital tract diseases.…”
Section: Manipulation Of Endosomal Protein Sorting By Pathogensmentioning
confidence: 99%
“…IncE is one of the effector proteins localized on the inclusion membrane, which specifically interacts with SNX5/SNX6 and inhibits retromer‐ and SNX5/SNX6‐mediated endosomal trafficking. Structural studies from 3 different groups revealed that IncE binds to a conserved hydrophobic groove in the PX domain of SNX5. Although the exact inhibitory mechanisms exerted by IncE remain to be determined, 2 observations indicate that IncE may function through interfering with the interaction between SNX5 and its cargo, such as IGFR1 and CI‐MPR (Figure B).…”
Section: Manipulation Of Endosomal Protein Sorting By Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is unknown if Inc proteins can also act as structural components to bring and maintain the ER and the inclusion membrane in close apposition. C. trachomatis encodes more than 50 putative Incs and only some of them have known functions in C. trachomatis infection (24,28,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Recently, Mirrashidi et al (37) determined the Inc-human interactome from uninfected cells expressing C. trachomatis Inc proteins.…”
mentioning
confidence: 99%